'People don't get cancer, families do': Co‐development of a social physical activity intervention for people recently affected by a cancer diagnosis. (13th March 2022) - Milton, Karen; Poole, Karen; Cross, Ainslea; Gasson, Sophie; Gokal, Kajal; Lyons, Karen; Pulsford, Richard; Jones, Andy
Abstract: Objective: This research took a co‐design approach to develop a social intervention to support people affected by a cancer diagnosis to be physically active. Methods: We conducted semi‐structured interviews with five key stakeholder groups: (1) adults with a recent breast or prostate cancer diagnosis; (2) family and friends of cancer patients; (3) healthcare professionals; (4) physical activity providers; and (5) cancer charity representatives. Inductive content analysis was used to identify themes in the data. We then worked with a subset of participants to co‐develop the intervention. Results: Participants welcomed the idea of a social approach to a physical activity intervention. Input was received on the timing and format of delivery, how to communicate about physical activity to cancer patients and their family and friends and the types of physical activity that would be appropriate. Our findings suggest that interventions need to be flexible in terms of timing and delivery and offer a wide range of physical activity options. These findings directly informed the co‐development of 'All Together Active'. Conclusion: All Together Active is designed to support cancer patients and their family and friends to be active throughout treatment and beyond, benefiting their physical and mental health.